1998
DOI: 10.1677/joe.0.1560509
|View full text |Cite
|
Sign up to set email alerts
|

The localisation and expression of 5 alpha-reductase types I and II mRNAs in human hyperplastic prostate and in prostate primary cultures

Abstract: The expression and localisation of mRNAs for 5 reductase Type I (5 R-I) and Type II (5 R-II) isoenzymes in human benign prostatic hyperplasia (BPH) were investigated by RT-PCR and by in situ hybridisation (ISH) using digoxigenin labelled riboprobes. In addition, we also examined the isoenzymes mRNA expression in primary BPH cultures of separated stroma/fibroblast and epithelial cells to determine whether primary cultures are appropriate models in which to investigate 5 R activity and regulation. The results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
2
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 30 publications
5
24
2
2
Order By: Relevance
“…This is distinctive from earlier models where 5·-reductase activity was either absent or depleted and no previous system ever expressed both iso-enzymes simultaneously [11,21,22]. The properties of 5·-reductase activity in the coculture model resemble those which have previously been detected in the human tissue [22] and we have no reason to believe that these are any different.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This is distinctive from earlier models where 5·-reductase activity was either absent or depleted and no previous system ever expressed both iso-enzymes simultaneously [11,21,22]. The properties of 5·-reductase activity in the coculture model resemble those which have previously been detected in the human tissue [22] and we have no reason to believe that these are any different.…”
Section: Discussioncontrasting
confidence: 53%
“…This is distinctive from earlier models where 5·-reductase activity was either absent or depleted and no previous system ever expressed both iso-enzymes simultaneously [11,21,22]. The properties of 5·-reductase activity in the coculture model resemble those which have previously been detected in the human tissue [22] and we have no reason to believe that these are any different. Whilst earlier studies had indicated that only the 5·-RII iso-enzyme was present in the human prostate gland, there is now sufficient evidence derived from biochemical analysis at the mRNA and protein levels of tissues from BPH and cancer patients to demonstrate that both iso-enzymes are present in prostate tissue; these have been localised in both the fibroblast and epithelial components of the glands [22] and this is now confirmed by our co-culture system.…”
Section: Discussioncontrasting
confidence: 53%
“…The remaining DHT in the prostate is likely to be the result of type 1 5α–reductase, either coming from the 30% of DHT remaining in the serum of men given finasteride or from intraprostatic type 1 5α–reductase. Although initial studies did not demonstrate type 1 protein in human prostate, more recent studies indicate that both type 1 and type 2 mRNA, protein, and enzyme activity are indeed present in prostate tissue [64, 65, 66, 67, 68, 69, 70]. …”
Section: Endocrine Control Of Prostate Growthmentioning
confidence: 99%
“…5RI is transcribed in different androgen-dependent organs like the epididymis (18), the testis (19) and the prostate (20,21). The localisation of 5RI in the cell nucleus of human prostate cells (22) and the close spatial relationship to the androgen receptor in prostate, epididymidis and testis reported by Aumü ller et al, also suggest a functional connection between this isoenzyme and cellular androgen metabolism (19).…”
Section: Discussionmentioning
confidence: 99%